Legal Education in Understanding Intellectual Property Rights: The Importance of Protecting Creativity and Innovation Based on Artificial Intelligence for Generation Alpha - Setiawati, Diana; Maulani, Indah; Nirwa Rizkyana, Elsa; Tsalsabila Anadila, Kharisma (Universitas Muhammadiyah Magelang, 2025)
The rapid development of digital technology has brought significant changes to everyday life. Generation Alpha (children born after 2010) are growing up surrounded by technological advancements, which means they have been accustomed to using gadgets and social media from an early age. Today, the use of Artificial Intelligence (AI) as a tool to support content creation is becoming increasingly widespread, even among children. This phenomenon presents new challenges, particularly regarding the understanding of Intellectual Property Rights (IPR). A study by Hosting Advice found that nearly half (49%) of parents with children aged 7”“14 reported that their children are already familiar with AI. Meanwhile, data from the 2021 NeuroSensum study revealed that 92% of Generation Alpha children in Indonesia were introduced to digital devices at an early age, and 87% had interacted with social media before turning 13. These findings highlight the urgent need for proper legal education so that children can use technology creatively while also understanding its legal boundaries. This community engagement program was implemented in the form of a legal awareness session at SMP Al-Kautsar, Sukoharjo. The activity was carried out in collaboration with the Majelis Hukum dan Hak Asasi Manusia (HAM) Aisyiyah Sukoharjo and involved law students as part of the “Kampus Berdampak” (Campus with Impact) initiative. The program aimed to educate students about the use of AI in content creation and its connection to copyright, raise awareness of the risks of IPR violations among young generations, and strengthen collaboration between universities and schools through outreach activities. The session generated strong enthusiasm from the students, reflected in interactive discussions and numerous questions about how to use AI legally and ethically. Through this initiative, Generation Alpha students are expected to develop the ability to utilize digital technology creatively while also respecting and complying with applicable legal frameworks.